2020
DOI: 10.1002/hed.26094
|View full text |Cite
|
Sign up to set email alerts
|

African Head and Neck Society Clinical Practice guidelines for thyroid nodules and cancer in developing countries and limited resource settings

Abstract: BackgroundInternational thyroid nodule and cancer management guidelines generally fail to take into account potential limitations in diagnostic and treatment resources.MethodsThyroid cancer specialists from the African Head and Neck Society and American Head & Neck Society Endocrine Section developed guidelines for diagnosis and management of thyroid nodules and cancer in low resource settings. Recommendations were based on literature review and expert opinion, with level of evidence defined.ResultsUsing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…A spongiform or partially cystic nodule has a very low risk of malignancy and a pure round‐walled thyroid cyst considered benign. The size of the nodule combined with the degree of suspicion pattern on ultrasound is decisive for the need of US‐FNAB in accordance with current and local guideline recommendations 2,3 . Further, the described technique for US‐FNAB can also safely be used for cytological evaluation of cervical lymph nodes with ultrasound features suggestive of malignancy.…”
Section: Indicationsmentioning
confidence: 61%
“…A spongiform or partially cystic nodule has a very low risk of malignancy and a pure round‐walled thyroid cyst considered benign. The size of the nodule combined with the degree of suspicion pattern on ultrasound is decisive for the need of US‐FNAB in accordance with current and local guideline recommendations 2,3 . Further, the described technique for US‐FNAB can also safely be used for cytological evaluation of cervical lymph nodes with ultrasound features suggestive of malignancy.…”
Section: Indicationsmentioning
confidence: 61%
“…Despite the ethical and logistical challenges presented by a low‐resource environment, the survey respondents were in strong agreement that the much‐needed treatment of people in these regions is possible and often within reach. The African Head and Neck Society and an article by Cervenka et al suggest that successful treatment of head and neck cancers is possible in low‐resource environments with adaptation to treatment methodologies 13,14 . Cervenka et al specifically suggest that it often involves upfront surgical resection and any involved or at‐risk lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Since favorable long-term outcomes for AS in clinical trials performed in Kuma Hospital were published in 2014, an AS management approach to avoid overtreatment has gradually been considered as an alternative to immediate surgery in low risk PTMC patients 23 . In recently updated versions of national/institutional guidelines, AS is recommended as a first-line management approach for patients with low risk PTMC (Table 1, Supplementary Figure S1) 10,11,[24][25][26][27][28][29][30][31][32][33][34][35][36] . However, recommendations in China are inconsistent between health authorities and academic institutions, leading to confusion among surgeons.…”
Section: Changes In Guideline Recommendationsmentioning
confidence: 99%
“…However, some investigators have suggested that for papillary thyroid carcinoma (PTC), there is an epidemic of diagnosis rather than an epidemic of disease [3][4][5] . From 2002 through 2018, the number of new thyroid cancers rose 11.7-fold (48,621 vs. 567,233), but the number of deaths remained largely stable (35,375 vs. 41,071) 6,7 . Therefore, over diagnosis and overtreatment of papillary thyroid microcarcinoma (PTMC) have attracted great attention from the medical establishment, and from society as a whole.…”
Section: Introductionmentioning
confidence: 99%